Microwave assisted depolymerization of Polyethylene Terephthalate [PET] healthcare waste - Upasen, Chainarong (Animo Repository, 2008)
Polyethylene Terephthalate (PET) wastes generated in healthcare facilities that are considered non-hazardous has raised serious concerns for its final disposal. To overcome demerits of recycling and incineration as method of treating these waste, pyrolysis technology was used. Pyrolysis has an advantage to recover the value added products from PET such as liquid and gaseous fuel, activated carbon and monomer recovery. Pyrolysis through microwave irradiation is new technology that can heat objects more uniformly at the shorter time than conventional heating methods. Therefore, microwave pyrolysis was employed in this study as environmentally-sound technology to treat PET packaging from healthcare waste. In this study, microwave pyrolysis process was carried under nitrogen atmosphere. There are four parameters that were investigated; temperature (T), residence time (t), charcoal percentage (C) and particle size (S). The experimental results were used to identify the best value of parameters that give the highest decomposition. Each effect of parameters was statistically analyzed to represent the highest decomposition. The results obtained show that decomposition percentage was significantly affected by the temperature and the charcoal percentage. On the other hand, the effect of residence time and the effect of particle size were found to be not significant. The best parameters obtained 59.34% decomposition at 630C for 20 minutes, 17% of charcoal using 2 mm of PET particle size. Furthermore, at best condition, the percentage of each product was 40.66% of residual solid, 13.48% of oil and 45.86% of gaseous product. Analysis of the oil was conducted by GC-MS. The oil product mainly contained benzene, benzoic acid and biphenyl. Also, SEM-EDX analysis was used to classify element of the residual solid. The result shows that residual solid contained 49.81% carbon, 38.40% nitrogen and 11.32% oxygen.